Descriptive content analysis of Philippine mythology as portrayed in selected graphic novels in the Philippines - Detoyato, Kristine Marie A.
This study aims to provide a list of suggested graphic novels for librarians who wish to add such into their collections, as well as illustrate the value of the selected graphic novels as a means of propagating Filipino culture by measuring the amount of content related to Philippine mythology. This was done by quantifying the characters that are based on Philippine myths and legends, then utilizing descriptive content analysis. This study also provides a short assessment of the intrinsic quality of each title covered. From the descriptive content analysis that was conducted on 14 selected graphic novels, it was found that the amount of Philippine mythology content varies for each title. Although 20.7% of the portrayals may subvert or modernize characterization of a certain mythological creature or character, a majority of 69.4% are loyal to the original myths. It was also found that the number of characters based on Philippine myths has a high positive correlation to the publication year of a graphic novel. The evaluation of intrinsic merits resulted in 13 of the 14 selected graphic novels were rated either for teens or for a mature audience and could stand the test of time in regards to the language of dialogue and references to pop culture. However, half of the titles are currently unavailable in major bookstores in Metro Manila. This may be problematic to those who wish to acquire those titles.